2017
DOI: 10.1111/cge.12951
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of ATP7B mutations and genotype–phenotype correlation in large‐scale Chinese patients with Wilson Disease

Abstract: Wilson disease (WD), an inherited disorder associated with ATP7B gene, has a wide spectrum of genotypes and phenotypes. In this study, we developed a rapid multiplex PCR-MassArray method for detecting 110 mutant alleles of interest, and used it to examine genomic DNA from 1222 patients and 110 healthy controls. In patients not found to have any mutation in the 110 selected alleles, PCR-Sanger sequencing was used to examine the ATP7B gene. We identified 88 mutations, including 9 novel mutations. Our analyses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 43 publications
6
36
1
Order By: Relevance
“…A relative high proportion of patients in this large WD cohort (21%) had only one detectable mutation, and similar data were reported by other studies . This is in contrast to the surprisingly 98%‐100% detection rate of two mutations in the much smaller studies .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A relative high proportion of patients in this large WD cohort (21%) had only one detectable mutation, and similar data were reported by other studies . This is in contrast to the surprisingly 98%‐100% detection rate of two mutations in the much smaller studies .…”
Section: Discussionsupporting
confidence: 90%
“…A relative high proportion of patients in this large WD cohort (21%) had only one detectable mutation, and similar data were reported by other studies. (25)(26)(27) This is in contrast to the surprisingly 98%-100% detection rate of two mutations in the much smaller studies. (28,29) There are several differences compared with our study that can explain the observed differences in mutation detection rate-most importantly, the lack of a clinical description of the patients in the UK study.…”
Section: Discussionmentioning
confidence: 61%
“…In patients with untreated WD, serum copper and ceruloplasmin levels are decreased with increased urinary copper excretion, and the free copper level may increase to more than 25 µg/dL 2. In a previous study, the serum ceruloplasmin level is lower in the neurological subgroup (<8 mg/dL) than in the hepatic subgroup 13. In the present study, all biochemical values involved in copper metabolism, including serum and free copper, ceruloplasmin, and urinary copper excretion levels, were decreased in the neurological subgroup.…”
Section: Discussionsupporting
confidence: 55%
“…In Asia, p.R778L (c.2333 G > T, exon 8) has been identified as the most common ATP7B variant, with a frequency of 17.3–31.9% reported in China (Cheng et al, ; X. H. Li et al, ; Mak et al, ; Wan et al, ). However, WD also exhibits genetic heterogeneity, as several studies have reported a much higher frequency of heterozygotes than homozygotes (Cheng et al, ; Hua et al, ; Xie & Wu, ). WD was initially considered to be a recessive genetic disorder but this is inconsistent with the high frequency of heterozygous mutations identified, of which the effects on ATP7B are mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have focused on either unrelated individuals (Cheng et al, ; Coffey et al, ; Y. Dong et al, ) or case reports or series of a limited number of pedigrees (Dufernez et al, ; Yuan et al, ; Zhang et al, ); moreover, direct experimental evidence of the functional consequences of individual ATP7B variants is still lacking. Here, to perform a systemic analysis of the genotypes of WD patients in China, we recruited 65 Chinese WD patients from 60 families for DNA sequencing.…”
Section: Introductionmentioning
confidence: 99%